PENGARUH PERUBAHAN IKLIM DAN MOBILITAS PENDUDUK TERHADAP KETIMPANGAN PEMBANGUNAN DI IDONESIA - Padang, Rikanesa; Mellita Sari, Cut Putri (Jurnal Ekonomi Regional Unimal, 2025)
This study aims to analyze the influence of climate change and population mobility on development inequality in Indonesia. This study uses secondary data from 2000 to 2023 obtained from the Central Statistics Agency. The data analysis method used is multiple linear regression analysis. The results show that climate change has a positive and significant effect on development inequality in Indonesia. Population mobility has a negative and significant effect on development inequality in Indonesia. Simultaneously, climate change and population mobility have a negative and significant effect on development inequality in Indonesia.